2016
DOI: 10.4103/0259-1162.165513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrathecal clonidine versus fentanyl on bupivacaine spinal block in transurethral resection of prostate surgeries

Abstract: Aims:Our study aimed at comparing the onset, degree and recovery time of sensory and motor block, the hemodynamic effects and postoperative pain relief using intrathecal bupivacaine alone, bupivacaine along with fentanyl and clonidine.Materials and Methods:A total of 90 patients, undergoing transurethral resection of prostate (TURP) surgeries under spinal anesthesia were studied. Patients were randomly divided in a double-blind manner into three groups of 30 patients each. Group A (control) patients given suba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…in their study in patients posted for transurethral resection of prostate concluded that intrathecal clonidine in a combination with bupivacaine provides more satisfactory anesthesia and analgesia and has less side effects compared to fentanyl which was similar to our finding. [ 28 ] All above studies have used intrathecal clonidine in doses from 15 μg to 150 μg, but use of intrathecal clonidine in dose of 50 μg provided prolonged postoperative analgesia with minimum side effects compared to fentanyl and other different doses of clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…in their study in patients posted for transurethral resection of prostate concluded that intrathecal clonidine in a combination with bupivacaine provides more satisfactory anesthesia and analgesia and has less side effects compared to fentanyl which was similar to our finding. [ 28 ] All above studies have used intrathecal clonidine in doses from 15 μg to 150 μg, but use of intrathecal clonidine in dose of 50 μg provided prolonged postoperative analgesia with minimum side effects compared to fentanyl and other different doses of clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated heating value of rice husk is approximately 15 MJ/kg [18]. In Asia and Africa, the annual generation of rice husk is 1.5 × 10 11 kg [64].…”
Section: Different Biomass Feedstock Materialsmentioning
confidence: 99%